1981
DOI: 10.1152/ajpgi.1981.240.2.g163
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal gastrin receptor. V. Development in newborn rats

Abstract: We determined the development of the oxyntic gland mucosal gastrin receptor in rats killed at various times from 5 to 60 days after birth. Rats were weaned on the 18th day after birth. Newborn animals had no detectable gastrin binding, high serum gastrin levels (800-1,200 pg/ml), low antral gastrin levels (0.5-2.0 micrograms/g tissue), or high pH of gastric contents (pH greater than 5.0) and did not respond to pentagastrin. At the time of weaning, serum gastrin dropped to 600 pg/ml and reached adult levels (30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
2
2

Year Published

1982
1982
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 0 publications
2
42
2
2
Order By: Relevance
“…has been reported to be refractory to gastrin-and its analogues due to the absence of specific gastrin receptors during the suckling period (21). From these studies, it appears quite probable that gastrin may be broken down to form a biologically active fragment which traverses the placenta and influences gastrin homeostasis in the contraplacental circulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…has been reported to be refractory to gastrin-and its analogues due to the absence of specific gastrin receptors during the suckling period (21). From these studies, it appears quite probable that gastrin may be broken down to form a biologically active fragment which traverses the placenta and influences gastrin homeostasis in the contraplacental circulation.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this possibility, we earlier reported evidence that tissue gastrin levels are abnormally elevated in the unborn fetuses of rats that had sustained an experimentally induced gastrin deficiency (13). On the other hand, there is evidence of hyposecretion of acid in several species examined during the period of neonatal hypergastrinemia (8,17,21,26), suggesting that an open negative feedback loop may also contribute to the elevation of serum gastrin levels at birth.…”
Section: Discussionmentioning
confidence: 99%
“…The neonatal rat gastric mucosa is also insensitive to gastrin during the preweaning period, and this has been found to be caused by absence of the receptors for the hormone (30). In the rat, mucosal gastrin receptors appear at the normal time for weaning, even if weaning to solid chow is artificially delayed.…”
Section: Discussionmentioning
confidence: 99%
“…Ligand binding studies have shown an increase in the number of cholinergic receptors with age in the CNS (1 1) vas deferens (12) and an increase of gastrin receptors on the parietal cell of the stomach during the newborn period (13). Functionally, the parietal cell does not produce acid in response to exogenous gastrin in the immediate newborn period in the rat, and shows increasing levels of responsiveness at the time of weaning, coincident with the emergence of gastrin receptors as detected by ligand binding studies (14,15).…”
Section: Electrical Stimulationmentioning
confidence: 99%